Sintesis dan Karakterisasi Bioplastik Berbasis Pati dengan Modifikasi Jenis Filler - Amelia Naomi Agustina; Denny Hendrik Nainggolan; Jonathan Ernest Sirait; Maghfira Arum Lestari (UNIVERSITAS ISLAM SYEKH YUSUF TANGERANG, 2026)
The development of starch-based bioplastics is an innovative strategy for diversifying petrochemical industry products toward bio-based materials while simultaneously contributing to reducing the accumulation of persistent conventional plastic waste in the environment. Furthermore, the development can enhance the utilization of biological resources and agro-industrial waste more sustainably within a circular economy framework. However, starch-based bioplastics generally have weaknesses in mechanical properties and swelling capability. This study aims to synthesize starch-based bioplastics by modifying the type of filler and strach to improve physical, mechanical, and stability characteristics. The synthesis is carried out by mixing and gelatinizing starch with the addition of sorbitol as plasticizer with several types of starch and filler with certain compositions. Characterization is carried out on mechanical and physical properties. In addition, swelling capacity test and biodegradability test are conducted. The results showed that variations in types of starch and fillers affect the characteristics of the resulting bioplastics and optimization is needed so that the resulting material has the potential to be applied to environmentally friendly and sustainable packaging materials.